Epoxyeicosatrienoic acid analog attenuates the development of malignant hypertension, but does not reverse it once established: a study in Cyp1a1-Ren-2 transgenic rats - Jíchová, Šárka (J Hypertens, 2016)
OBJECTIVE: We evaluated the therapeutic effectiveness of a new, orally active epoxyeicosatrienoic acid analog (EET-A) in rats with angiotensin II (ANG II)-dependent malignant hypertension. METHODS: Malignant hypertension was induced in Cyp1a1-Ren-2 transgenic rats by activation of the renin gene using indole-3-carbinol (I3C), a natural xenobiotic. EET-A treatment was started either simultaneously with I3C induction process (early treatment) or 10 days later during established hypertension (late treatment). Blood pressure (BP) (radiotelemetry), indices of renal and cardiac injury, and plasma and kidney levels of the components of the renin–angiotensin system (RAS) were determined. RESULTS: In I3C-induced hypertensive rats, early EET-A treatment attenuated BP increase (to 175 ± 3 versus 193 ± 4 mmHg, P < 0.05, on day 13), reduced albuminuria (15 ± 1 versus 28 ± 2 mg/24 h, P < 0.05), and cardiac hypertrophy as compared with untreated I3C-induced rats. This was associated with suppression of plasma and kidney ANG II levels (48 ± 6 versus 106 ± 9 and 122 ± 19 versus 346 ± 11 fmol/ml(−) or g, respectively, P < 0.05) and increases in plasma and kidney angiotensin (1–7) concentrations (84 ± 9 versus 37 ± 6 and 199 ± 12 versus 68 ± 9 fmol/ml or g, respectively, P < 0.05). Remarkably, late EET-A treatment did not lower BP or improve renal and cardiac injury; indices of RAS activity were not affected. CONCLUSION: The new, orally active EET-A attenuated the development of experimental ANG II-dependent malignant hypertension, likely via suppression of the hypertensiogenic axis and augmentation of the vasodilatory/natriuretic axis of RAS.